COVID-19 raises a health and human rights imperative to advance a UN Convention on the Rights of Older Persons - Benjamin Mason Meier; Victoria Matus; Maximillian Seunik (BMJ Global Health)
The COVID-19 pandemic has revealed the inequitable health harms and human rights violations faced by older persons, raising a need to support healthy ageing policy as a human rights imperative. However, international human rights law has long neglected the health-related human rights of older persons. Drawing from evolving advocacy efforts to advance the rights of older persons through the United Nations (UN), tentative initial steps have been taken at the regional level, with states in the Americas codifying intersectional rights obligations underlying health through the Inter-American Convention on Protecting the Human Rights of Older Persons. These international and regional efforts provide a foundation to advance the right to health for older persons. Amid an ongoing demographic transition and an inequitable pandemic response, the prospective UN Convention on the Rights of Older Persons provides a crucial opportunity to elaborate and uphold the international legal obligations necessary to facilitate healthy ageing.